Global asymptotic synchronization for delayed inertial BAM neural networks without controllers via the fundamental solution matrix method - Shuai, Yiping; Zhang, Zhengqiu; Dai, Zhibin (Nonlinear Analysis: Modelling and Control, 2026)
This paper considers the global asymptotic synchronization (GAS) for master-slave delayed inertial bidirectional associative memory (BAM) neural networks (NNs). Most existing studies on GAS rely on the LMI approach, integral inequality, matrix measure, and maximum-valued methods, usually with additional controllers. In contrast, this work achieves GAS without using the above methods or designing any controllers. Instead, two new sufficient conditions are derived via the fundamental solution matrix method for first-order differential systems. For the first time, the fundamental solution matrix method is introduced to deal with the GAS for the NNs.